Perceptions Governing Sustainability in the Construction Sector of the United Arab Emirates - Abdulmaksoud, Sara Adel Abdulwahab (2022)
A Master of Science thesis in Construction Management by Sara Adel Abdulwahab Abdulmaksoud entitled, “Perceptions Governing Sustainability in the Construction Sector of the United Arab Emirates”, submitted in November 2022. Thesis advisor is Dr. Salwa Beheiry. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).